Analisis Rasio Keuangan Dalam Menilai Kinerja Keuangan Pemerintah Kabupaten Siak Tahun Anggaran 2012 - 2016 - Novira Sartika; Adrian Irnanda Pratama (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2019)
This study aims to determine the financial performance of the Siak Regency Government for the 2012-2016 fiscal year measured by financial ratio analysis. This research method is quantitative descriptive. The data are secondary data in the form of Budget Realization Report (LRA) for the 2012-2016 fiscal year. The analysis shows that the financial performance of the Siak Regency Government measured by ratio of regional financial independence shows very low with an average ratio of 9.83%. Furthermore, if measured by ratio of regional financial efficiency shows efficient with an average ratio of 67.51%. Then when measured by ratio of the effectiveness of Own-Source Revenue (PAD) shows effective with an average ratio of 112.51%. When observed by growth ratio shows fluctuation conditition. The Last, measured from the equivalent ratio, especially the ratio of operating expenditure show average ration 64.95% and capital expenditure 31.53%. We conclude that the financial performance of the Siak Regency Government is efficient in terms of spending expenses to obtain revenue with the realization revenue received by government and effective in order to increase revenue of Own-Source Revenue (PAD) to self-financing for government program due to society tend to pay tax and retribution. Beside that the government should maintan success from year to year and focus more on capital expenditure budgeting than operating expenditure budgeting.